2022
DOI: 10.1039/d2ra05679h
|View full text |Cite
|
Sign up to set email alerts
|

3D hierarchical cobalt vanadate nanosheet arrays on Ni foam coupled with redox additive for enhanced supercapacitor performance

Abstract: ASC device based on Co3V2O8 nanowalls, activated carbon and K3[Fe(CN)6]/KOH redox additive electrolyte shows an ultrahigh energy density of 55.5 W h Kg−1 at a power density of 800 W Kg−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…[ 37 ] This work uses only SS as a conductive substrate, which avoids the redox reaction in the alkaline electrolyte; hence the obtained SE and SP originated from the CVO1:1 and rGO materials. Moreover, the position of the HASD device in the Ragone plot is higher than SHSD and reported hybrid devices in terms of SP, without scarifying much SE, [ 11,16,49–56 ] suggesting the suitability of CVO1:1 thin film electrode for next‐generation hybrid energy storage devices.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…[ 37 ] This work uses only SS as a conductive substrate, which avoids the redox reaction in the alkaline electrolyte; hence the obtained SE and SP originated from the CVO1:1 and rGO materials. Moreover, the position of the HASD device in the Ragone plot is higher than SHSD and reported hybrid devices in terms of SP, without scarifying much SE, [ 11,16,49–56 ] suggesting the suitability of CVO1:1 thin film electrode for next‐generation hybrid energy storage devices.…”
Section: Resultsmentioning
confidence: 95%
“…Nguyen et al constructed a Co 3 V 2 O 8 //AC device and achieved SE of 55.5 Wh kg −1 at a higher SP of 800 W kg −1 . [ 50 ] Moreover, Sun et al [ 16 ] developed Co 2 V 2 O 7 ·3.3H 2 O//rGO, and Liu et al [ 51 ] prepared CoV 2 O 6 ·2H 2 O//AC devices reported SE of 19 Wh kg −1 at 375.8 W kg −1 SP and SE of 19 Wh kg −1 at 400 W kg −1 SP, respectively. Lv et al [ 52 ] fabricated Co 3 O 4 /CoV x O y //AC asymmetric device and reported SE of 26.1 Wh kg −1 at 400 W kg −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation